Screenwriting for dummies - Schellhardt, Laura (New Jersey Wiley Publishing, Inc., 2022)
You know that fantastic idea you've got for a screenplay? It's time to make it a reality! In this book, you'll learn how to move from concept to finished product with practical and hands-on advice on writing characters, dialogue and plot, talking to the right people, and marketing and selling your work.
Includes bibliographical references and index.
Keywords: Motion picture authorship